Controversias en síndrome de intestino irritable - Madrid S., Ana María; Landskron R., Glauben (Revista Hospital Clínico Universidad de Chile, 2010)
Irritable Bowel Syndrome (IBS) is a chronic and recurrent functional digestive disorder, characterized by abdominal pain or discomfort associated to stool change in frequency and/ or consistency, usually relieved with defecation and sometimes accompanied by abdominal distension. This syndrome is one of the most prevalent worldwide and is the most frequent cause of ambulatory consults. In Santiago, has a prevalence of 26%. The prevalence of other countries is not documented. IBS is 1.5-fold more likely in women. It has been reported that 9 – 22% of people says having symptoms of IBS, but only 9 – 33% of them actually consults for this cause. It is 12% of general practice; therefore, the acknowledgement of diagnostic criteria and therapeutic options is significant. These patients have clearly a lower quality of life. Currently diagnosis is made with Rome III Criteria, which have a high sensibility and specificity. It givesimportance to alarm symptoms when complementary studies are needed. The current treatment is in discussion, there is no one single drug that improves all symptoms and therapies are associated between diet, antispasmodics, antidepressives, psychotherapy, etc. In this review we will analyze each subject literature has mentioned as controversial in IBS management